Proposed outlining exercises for the first year - Rillera, Fe N. 1925- (s.n.], 1967)
The aim of this study is to propose a set of outlining exercises intended for first year high school students. Selections included were taken from the basic readers used in Grades V and VI. The exercises were arranged in different levels of difficulty over a wide range of topics in which to practice outlining.